Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.3758/bf03206911
|View full text |Cite
|
Sign up to set email alerts
|

Training Japanese listeners to identify English /r/and /l/: Long-term retention of learning in perception and production

Abstract: Previous work from our laboratories has shown that monolingual Japanese adults who were given intensive high-variability perceptual training improved in both perception and production of English Iri-ill minimal pairs. In this study, we extended those findings by investigating the long-term retention of learning in both perception and production of this difficult non-native contrast. Results showed that 3 months after completion of the perceptual training procedure, the Japanese trainees maintained their improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
264
8
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(310 citation statements)
references
References 22 publications
18
264
8
8
Order By: Relevance
“…For example, improved intelligibility has been found after sufficient exposure to synthetic speech (Greenspan, Nusbaum, & Pisoni, 1988;Maye, Aslin, & Tanenhaus, 2003), compressed speech (Dupoux & Green, 1997;Mehler et al, 1993), and nonnative accented speech (Bradlow & Bent, 2003;Bradlow, Pisoni, Akehane-Yamada, & Tohkura, 1997;Bradlow, Akehane-Yamada, Pisoni, & Tohkura, 1999). Clearly, listeners learn something about the speech they are exposed to and use what they learn to improve their perception of similar speech.…”
Section: Introductionmentioning
confidence: 99%
“…For example, improved intelligibility has been found after sufficient exposure to synthetic speech (Greenspan, Nusbaum, & Pisoni, 1988;Maye, Aslin, & Tanenhaus, 2003), compressed speech (Dupoux & Green, 1997;Mehler et al, 1993), and nonnative accented speech (Bradlow & Bent, 2003;Bradlow, Pisoni, Akehane-Yamada, & Tohkura, 1997;Bradlow, Akehane-Yamada, Pisoni, & Tohkura, 1999). Clearly, listeners learn something about the speech they are exposed to and use what they learn to improve their perception of similar speech.…”
Section: Introductionmentioning
confidence: 99%
“…Production accuracy was judged by a group of naive American listeners. In addition to perceptual improvements, Bradlow et al (1997;Bradlow et al, 1999) found moderate but significant improvements in production. Like the perceptual gains, those in production were intact after a three-month period with no additional training.…”
mentioning
confidence: 99%
“…This difference reflects an inherent tension that must be resolved in a learning system: Specifically tuning the representations/ processes for the training input may optimize performance on the stimuli prevailing in the environment, but there are also advantages to being able to generalize the learning to new sources. Bradlow, Pisoni, Akahane-Yamada, and Tohkura (1997;Bradlow, Akahane-Yamada, Pisoni, & Tohkura, 1999) tested whether the gains made with perceptual training also enhance the ability of Japanese speakers to produce the English / /-/ / distinction. Bradlow et al (1997;Bradlow et al, 1999) used training procedures similar to those of Lively et al (1994), and measured both perceptual and production accuracy before and after the training regime.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to train motivated learners on difficult sound contrasts-for example, efforts to teach native speakers of Japanese to hear differences between /l/ and /r/ sounds-usually show modest gains after many hours of training. 10 Some people learning a new language reach native-like performance, but most fall short of that goal, even after a lifetime's immersion. 11 Many factors make it hard to learn the sounds of a new language.…”
Section: Sound To Meaningmentioning
confidence: 99%